Distal brachyphalangy of the thumb in mental retardation. - Villaverde, M M (1975)
Distal brachyphalangy (DBP) of the thumbs is a hereditary autosomal anomaly found in 1 to 1.5% of whites and in less than 1% of blacks. It was found in 26 of 852 mentally retarded patients in the present study; a frequency of over 3%. The male:female ratio was 70:30. There was bilateral DBP IN 69.5% and unilateral DBP on the right hand in 19% and on the left in 11.5%. The 26 cases (100%) showed a subsyndromic aggregate of distal brachyphalangy of the thumb (DBT), short stature and mental retardation, 19 of them presented an abnormal head and 17 presented abnormal feet (nine of them also had convulsions). Six cases are discussed in detail; it is suggested that they belong to particular clinical categories. In addition to gene abnormalities (which is the most likely cause) a possible explanation of the aetiological factors could be found in some sort of anomaly of the hypopituitary-hypothalmic area, since in the five cases where it was investigated, the sella turcica was small in four cases and large in one. Almost all known syndromes of which the subsyndrome discussed here is a part also shown abnormal skulls, and this may add to the aetiology.